On the Ultrasonic Atomization of Liquids - Gaete-Garreton, L; Vargas-Hernandez, y; Salinas-Barrera, V; Briceno-Gutierrez, D (Elsevier B.V., 2015)
This paper deals with an experimental study of liquid atomization phenomena. For this study an experimental set-up was designed and constructed. A special criterion to start the recording of the process with a high speed digital camera was developed. The frequency dependence of atomization threshold is considered. The theoretical predictions for atomization threshold are also checked. The agreement between the predictions and the experimental results fit qualitatively with the data well until a frequency of 22 kHz. For frequencies beyond this value the tendencies are the opposite. © 2015 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license.